Climate change, catastrophic risk and the relative unimportance of discounting - Eric Nævdal; Jon Vislie (University of Oslo, Department of Economics, 2008)
Discounting in the presence of catastrophic risk is a hotly debated issue, in particular with respect to climate change. Many scientists and laymen concerned with potentially catastrophic impacts feel that if an increase in the discount rate drastically increases the likelihood of catastrophic outcomes, this discredits economic cost-benefit calculations. This paper argues that this intuition is sound and that if cost-benefit calculations are done within a model that encompasses the type of catastrophic risk that these scientists worry about, the resulting stabilization target will only be slightly influenced by the discount rate. This is shown within a stylized model of a risk neutral decision maker facing a problem with a catastrophic threshold with unknown location.
Keywords: 330; climate change; discounting; catastrophic risk; optimal control; Naturkatastrophe; Klimaveränderung; Abzinsung; Kosten-Nutzen-Analyse; Theorie